Creation or translation? Bilingual campaigns in Basque advertising agencies (Communication & Society, 2013)
Scientific research to date has not focused on the issue of bilingualadvertising creation. As a contribution to this line of research, this article uses a specific sociolinguistic approach, taking the Basque country as its model. Thus, using semi-structured in-depth interviews, it describes the internal processes that major advertising agencies follow in order to create advertisements in two official Languages, Basque and Spanish. The study highlights the fact that the creation process is primarily in Spanish, adapting to Basque at a later date, a fact which has repercussions on the effectiveness of the campaigns in the second language. The main conclusion shows a need to define and design a prototype model of bilingual development, which at the present time is nonexistent.